Kids can draw fairy tales : a child's first drawing book - Legendre, Philippe (Laguna Hills, CA : Walter Foster Publishing, 1996)
Fairy tales are featured in this book, which teaches young children how to transform simple circles, squares and triangles into art by featuring their favorite subjects, such as dinosaurs, fairy tales and animals. Each book in this series shows how to draw nine pictures.
Keywords: Drawing -- Technique -- Juvenile literature; Fairy Tale Illustrations -- Technique -- Juvenile literature